A Novel Algorithm for the Evaluation of Corneal Nerve Beadings by in vivo Confocal Microscopy in Patients With Type 1 Diabetes Mellitus - Irene Abicca; Daniela Giannini; Marta Gilardi; Anna Maria Roszkowska; Mariacristina Parravano; Fabiana Picconi; Simona Frontoni; Simona Frontoni; Domenico Schiano-Lomoriello (Frontiers in Medicine, 2022)
PurposePeripheral neuropathy could complicate diabetes mellitus (DM). In vivo confocal microscopy (IVCM) is an ocular examination for the diagnosis of small fiber neuropathies and the detection of the earliest corneal sub-basal nerve plexus (SBP) alterations. Corneal SBP characteristics include focal enlargement along with the nerve fiber, called corneal beadings. These dilatations represent a mitochondrial accumulation induced by the reactive oxygen stress, as a consequence of hyperglycemia. For this reason, corneal beadings are considered indicative of metabolic activity. This study aimed to describe the corneal characteristics of a population of type 1 diabetes mellitus (T1DM) well metabolically controlled, using a new algorithm for the analysis of corneal beading size (BS).MethodsPatients aged ≥18 years affected by T1DM were compared with healthy subjects who underwent IVCM (Confoscan 4; Nidek Technologies Padova, Italy). Starting from the coordinates of the beadings detected by the IVCM, we implemented a new algorithm for automatically measuring BS in corneal SBP images.ResultsWe compared 20 eyes of T1DM patients with 26 healthy controls. The corneal nerves' fiber length (p = 0.008), corneal nerves' fiber length density (p = 0.008), and the number of fibers (p = 0.017) were significantly lower in the diabetic group compared with controls. There was no difference between diabetic and healthy eyes in the mean number of corneal beadings both in the frame of analysis (p = 0.606) and for 0.1 mm of SBP nerve (p = 0.145). Regarding the BS, patients with T1DM had corneal beadings larger than controls (p = 0.036).ConclusionsWe found that the corneal beadings parameters are similar in healthy and T1DM individuals. Nevertheless, measuring the BS with our algorithm, we showed that corneal beadings are enlarged in patients affected by T1DM when compared with healthy controls. Identifying beading expansion in corneal nerve fiber using IVCM should become a useful tool to predict peripheral neuropathy at an early stage.